Geomechanics and Engineering Evaluation of Fractured Oil and Gas Reservoirs: Progress and Perspectives - Hu Li; Xiaodan Gao; Ahmed E. Radwan; Haijun Wang; Shuai Yin (Energies)
Unconventional oil and gas exploration and development are entering an era of interdisciplinary technological revolution [...]